Child drowning deaths in Xiamen city and suburbs, People's Republic of China, 2001–5. Issue 5 (4th October 2007) - Fang, Ya; Dai, Long; Jaung, Michael S; Chen, Xiaoxuan; Yu, Songlin; Xiang, Huiyun
Abstract : Background: Risk-factor research and prevention programs targeting drowning deaths in children have been well developed in industrialized countries, but little research has been undertaken in developing countries where the majority of drowning deaths occur. We conducted an epidemiological study to describe the sociodemographic characteristics, drowning circumstances, and medical service in drowning deaths of children in Xiamen city and suburbs, People's Republic of China. Material and methods: Drowning deaths in 1–14-year-old children between 2001 and 2005 were identified using death certificates. Parents of each case were interviewed face to face about the sociodemographics of the family and child, the drowning event, and medical care received. Mortalities were calculated using census data for urban and rural areas, and Poisson regression was used to evaluate confounding effects and interactions of several major risk factors for drowning death. Results: Of 67 drowning deaths identified, 52 (77.6%) were males. A higher proportion of deaths were in children aged 5–9 years (40.3%) and 10–14 years (40.3%). The drowning mortality per 100 000 population was 5.84 in rural areas and 0.75 in urban areas. Drowning events occurred most commonly during the summer months (56.7% from June to August), during the hours of 13:00–17:59 (62.7%), and in natural or man-made bodies of water (eg, ponds, ditches, construction sites, and wells). None of the children were proficient swimmers, the majority of drowning events (88.1%) occurred in the absence of adult supervision, and 86.6% children died at the scene without any medical care. Results from muiltivariable Poisson regression analysis indicated that 10–14-year-old boys were at the highest risk of drowning deaths in this area. Discussion and conclusions: Drowning deaths in children in Xiamen city and suburbs follow trends that are markedly different from patterns observed in other countries. Different prevention strategies may be required for preventing child drowning deaths in Xiamen and other developing regions.